[Zn2+–Ge4+] co-substitutes [Ga3+–Ga3+] to coordinately broaden the near-infrared emission of Cr3+ in Ga2O3 phosphors. Issue 3 (23rd December 2022) - Lin, Jianhua; Zhou, Liuyan; Shen, Yuyu; Fu, Jie; Chen, Yanling; Lei, Lei; Ye, Renguang; Shen, Yang; Deng, Degang; Xu, Shiqing
Abstract : This paper focuses on the use of [Zn 2+ –Ge 4+ ] to co-replace [Ga 3+ –Ga 3+ ], which redshifts the near-infrared emission of Cr 3+ in Ga2 O3, and broadens the full width at half maximum. Abstract : Here, a "chemical unit co-substitution" method is used to improve the near-infrared (NIR) emission of phosphors, using [Zn 2+ –Ge 4+ ] to co-substitute [Ga 3+ –Ga 3+ ] sites to reduce crystal field splitting to affect the structure of gallium oxide. A series of broadband NIR phosphors are synthesized by a high-temperature solid-phase method, and their phase structures, crystal structures, morphologies, diffuse reflectance spectra, and luminescence lifetimes are investigated. The Ga1.68 (Zn–Ge)0.3 O3 :0.02Cr 3+ (GZGOC) phosphor exhibits NIR wide-band emission, with a peak wavelength of 766 nm and a half-width of 138 nm. Meanwhile, the quantum yield of photoluminescence can reach 81.2%. The phosphor has good thermal stability. When the temperature reaches 373 K, its emission intensity still remains at 73.4% of that at room temperature. A 460 nm LED chip and this phosphor are used to fabricate a phosphor-converted light emitting diode (pc-LED) device which can be used as a NIR light source. All these results show the application potential of the as-prepared phosphor in NIR imaging.